#### Answer

1. The second term is 10
2. The third term is 11.2
3. The fourth term is 12.4
4. The explicit formula is A(n)=8.8+1.2(n-1)

#### Work Step by Step

A(1)=8.8
A(n)=A(n-1)+1.2
1. The second term is
A(2)=A(2-1) +1.2 = A(1)+1.2 = 8.8 +1.2 = 10
2. The third term is
A(3)=A(3-1)+1.2 = A(2)+1.2 = 10+1.2 = 11.2
3. The fourth term is
A(4)=A(4-1)+1.2 = A(3)+1.2 = 11.2 +1.2 = 12.4
4. The explicit formula is A(n)=8.8+1.2(n-1)
Because the sequence is in the form of A(n)=A(1)-d(n-1) and the value of A(1) is 8.8 and the value of d is 1.2 as it was derived from the recursive formula and also from the sequence.